2015
DOI: 10.1007/s12221-015-1349-2
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical response and failure of 3D MWK carbon/epoxy composites at cryogenic temperature

Abstract: Static tensile and bending experiments are conducted on 3D MWK carbon/epoxy composites with two types of fiber architecture at room and cryogenic temperature (low as -196 o C). Macro-Fracture morphology and SEM micrographs are examined to understand the deformation and failure mechanism. The results show that tensile stress vs. strain curves have linear elastic feature up to failure; while the load-deflection curves for composites with large fiber orientation angle have pronounced nonlinear and failure in step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Luo et al [32] coated PVC on bi-axial warp knitted fabric and demonstrated that the coated fabric exhibited anisotropic properties under both mono-axial and multiaxial tensile loads. Li et al [33][34][35] studied the tension fatigue behavior and failure mechanism of 3D MWK composites, and their tensile and bending properties at cryogenic temperature. Ma et al [36] added short glass fibers between MWK fabric layers to improve interface strength.…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al [32] coated PVC on bi-axial warp knitted fabric and demonstrated that the coated fabric exhibited anisotropic properties under both mono-axial and multiaxial tensile loads. Li et al [33][34][35] studied the tension fatigue behavior and failure mechanism of 3D MWK composites, and their tensile and bending properties at cryogenic temperature. Ma et al [36] added short glass fibers between MWK fabric layers to improve interface strength.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Yudhanto et al 19,20 studied the effect of stitching on compression properties and damage mechanisms and indicated that stitching generally reduces the compression strength of carbon/epoxy composites. Li et al [21][22][23] presented an experimental study on tensile, bending, dynamic properties, and failure mechanism for 3-D MWK composites at different temperatures and showed the fiber architecture and environment temperature are important factors influencing mechanical properties of composites.…”
Section: Introductionmentioning
confidence: 99%
“…They provided full data on the bending behavior in the broad range of the radii of curvature. Li et al [22] studied bending properties of composites at cryogenics temperature and found the properties at liquid nitrogen temperature have been improved significantly. The previous studies have shown that the fiber architecture, environment temperature and fiber volume fraction are important factors which can affect the bending properties of composites, and the failure mechanisms of the MWK composites have some correlations with the manufacture processing parameters.…”
Section: Introductionmentioning
confidence: 99%